1994
DOI: 10.1210/en.135.5.1996
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding protein-2 and -3 are correlated with atresia and preovulatory maturation in the porcine ovary

Abstract: We compared insulin-like growth factor-binding protein (IGFBP) levels with indicators of follicular maturation and atresia in individual follicles of the porcine ovary. Follicular development was synchronized with the progestin, altrenogest, and progestin withdrawal was used to initiate the growth of an ovulatory cohort of follicles, which is accompanied by atresia of noncohort follicles. Individual follicles were isolated on days 1, 3, 5, and 7 after progestin withdrawal. Atretic follicles were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
7
19
0
Order By: Relevance
“…In the present study levels of lGFBP-2 in FFL from small follicles were increased by GRFi while IGFBP-3 levels were decreased. Recently Grimes et al (41) reported a positive correlation between FFL lGFBP-3levels and follicle diameter in the porcine ovary (41). In contrast, lGFBP-2 was found to be related more to atresia than to follicle size, suggesting specific roles for individual forms of lGFBP.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study levels of lGFBP-2 in FFL from small follicles were increased by GRFi while IGFBP-3 levels were decreased. Recently Grimes et al (41) reported a positive correlation between FFL lGFBP-3levels and follicle diameter in the porcine ovary (41). In contrast, lGFBP-2 was found to be related more to atresia than to follicle size, suggesting specific roles for individual forms of lGFBP.…”
Section: Discussionmentioning
confidence: 97%
“…2). By contrast, in sheep and pig, growth of follicles is characterized by a slight increase in intrafollicular IGFBP-3 levels [19,21], Moreover, in the sheep, atresia of small follicles is characterized by a decrease in intrafollicular IGFBP-3 levels [21 ]. The mech anisms that lead to such observed changes in intrafollicu lar IGFBP-3/IGFBPs<40 kD ratio are likely different for IGFBPs <40 kD and IGFBP-3.…”
Section: Changes In Intrafollicular Igfbp Levels During Growth and Atmentioning
confidence: 99%
“…We have described the changes in concentration of ovarian steroids and in expression of several peptides associated with apoptosis and cell proliferation in vivo during two stages of follicular development in pigs [7,[10][11][12][13][14][15][16]. However, in vitro model systems are needed for pigs for the investigation of factors that regulate proliferation and death at the cellular level.…”
Section: Introductionmentioning
confidence: 99%